Some aspects of the nonlinear interaction between global teleconnection patterns - Glushkov, A.V.; Loboda, N.S.; Khokhlov, V.N.; Svinarenko, A.A.; Serbov, N.G.; Bunyakova, Yu.Ya. (Український антарктичний журнал, 2008)
The chaotic behavior in the global climate system of the Earth and the nonlinear interaction between some teleconnection patterns during different epochs of the twenty century are studied. To study the influence of low frequency variations, the wavelet decomposition is applied. We use the cross-redundancy and Granger causality for detailed componentsof the wavelet decomposition.